The paradox of better population health after the pandemic: what is the cause? - Biernacki, Marek; Ostasiewicz, Katarzyna (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to verify the hypothesis that the improvement in the subjective assessment of population health in certain European countries after the COVID-19 pandemic was driven by the mortality of the majority of vulnerable citizens with the worst health status.MethodsWe extended the trend of the share of the oldest age group and compared it with the observed fraction, thereby identifying the “missing population.”ResultsWe observed a substantial deficit in the population of the oldest age group, especially in countries where people tend not to age well.ConclusionThe temporary improvement in population health indicators, as measured by Healthy Life Years (HLY), during the pandemic in some countries was most likely an artifact resulting from the mortality of the majority of vulnerable individuals with poor health status. It is unlikely that this apparent improvement reflects healthier lifestyles or genuine gains in the efficiency or resilience of health systems during the pandemic. Therefore, the interpretation and use of HLY values from the COVID-19 period in Europe should be carefully reconsidered and further validated.